Online Science Teaching and Learning Among Children During COVID-19 Pandemic - Sinha, Sharad (SCHOOL SCIENCE, 2021)
The paper examines the situation and emerging crisis in the pandemic and the condition of school education with special reference to science education. Continuing the education of students emerged as a major challenge during the unprecedented lockdown. Digital learning is a terrain which was not widely explored by the teachers for classroom teaching. The education sector in India is one important area that has been severely affected by the lockdown and the imposed restrictions. The study was conducted with 500 science teachers from 9 states on various pertinent points including awareness, preparedness mode, methods used teaching, usage of apps, managing-interactions, assignments and assessments during the COVID-19 pandemic